The Extremophile Endolithella mcmurdoensis gen. et sp. nov. (Trebouxiophyceae, Chlorellaceae), A New Chlorella‐like Endolithic Alga From Antarctica. Issue 1 (17th November 2019) - Martins, Teresa P.; Ramos, Vitor; Hentschke, Guilherme S.; Castelo‐Branco, Raquel; Rego, Adriana; Monteiro, Maria; Brito, Ângela; Tamagnini, Paula; Cary, S. Craig; Vasconcelos, Vitor; Krienitz, Lothar; Magalhães, Catarina; et al.
Abstract : The McMurdo Dry Valleys constitute the largest ice‐free region of Antarctica and one of the most extreme deserts on Earth. Despite the low temperatures, dry and poor soils and katabatic winds, some microbes are able to take advantage of endolithic microenvironments, inhabiting the pore spaces of soil and constituting photosynthesis‐based communities. We isolated a green microalga, Endolithella mcmurdoensis gen. et sp. nov, from an endolithic sandstone sample collected in the McMurdo Dry Valleys (Victoria Land, East Antarctica) during the K020 expedition, in January 2013. The single non‐axenic isolate ( E. mcmurdoensis LEGE Z‐009) exhibits cup‐shaped chloroplasts, electron‐dense bodies, and polyphosphate granules but our analysis did not reveal any diagnostic morphological characters. On the basis of phylogenetic analysis of the 18S rRNA (SSU) gene, the isolate was found to represent a new genus within the family Chlorellaceae.